Development of Microbial Fuel Cell in Tofu Liquid Waste in Producing Clean Energy - Tiara, Ansia; Ramadhani, Safira Redzy; Tuhuloula, Abubakar (Jurnal Bahan Alam Terbarukan, 2023)
The high need of Indonesian people for electrical energy has led to an increase in energy demand. This has triggered research efforts based on renewable technologies that are efficient and environmentally friendly. One of the renewable energy sources that is widely developed is Microbial Fuel Cell (MFC). MFC works by utilizing organic matter used by microbes as an energy source in carrying out metabolic activities. This study aims to determine the effect of Bacillus subtilis and Escherichia coli bacteria with different concentrations of 10% (v/v) and 15% (v/v) on the electrical energy generated from the tofu liquid waste substrate and observe changes in pH and Biological Oxygen Demand (BOD) in the MFC system. This research method consists of several steps, namely the preparation of electrolysis equipment, electrodes, substrates, bacterial cultures, electrolytes and MFC processes. The maximum value of voltage and current in Bacillus subtilis bacteria occurred at the 10 hours with 15% (v/v) bacterial concentration which amounted to 394 mV and 10.6 mA with a bacterial population of 16.15 × 109 CFU/mL and a power density value of 126.67 × 10-4 watt/m2. Furthermore, the maximum value for Escherichia coli bacteria occurred at the 10 hours with a voltage and current of 266 mV and 5.3 mA with a bacterial population of 15.60 × 109 CFU/mL and a power density value of 55.67 × 10-4 watts/m2. The pH value of the substrate variations with the addition of Bacillus subtilis bacteria ranged from 5-6, while with the addition of Escherichia coli bacteria variations ranged from 4-5. This system also reduces the value of biological oxygen demand.